Pengungkapan Sukarela Laporan Keuangan Tahunan Dan Faktor-Faktor Yang Mempengaruhi (Studi Pada Saham-Saham LQ45 Di Bursa Efek Indonesia Periode 2010-2011) - Baskaraningrum, Made Ratih; Merkusiwati, Ni Ketut Lely A (E-Jurnal Akuntansi; Vol 2 No 1 (2013), 2013)
The study was conducted to determine the voluntary disclosure of annual financial statements LQ45 stocks and factors affecting. This study uses secondary data from annual financial reports LQ45 stocks. Sampling method using purposive sampling. Total population of 90 companies and the number of samples obtained by 30 companies.The analysis show that profitability, leverage, liquidity and managerial ownership does not have effect on voluntary disclosure, while the negative effect of firm size voluntary disclosure annual financial shares on the Stock Exchange LQ45 period2 010-2011. Keywords: profitability , leverage, liquidity, firm size, managerial ownership, voluntary disclosure